Avaliação do método de disco-difusão para determinação da eficácia da terbinafina in vitro em agentes de micoses superficiais e subcutâneas Evaluation of the disk-diffusion method to determine the in vitro efficacy of terbinafine against subcutaneous and superficial mycoses agents - Hilda Conceição Diogo; Márcia Melhem; Aldo Sarpieri; Mario Cezar Pires (Sociedade Brasileira de Dermatologia, 2010)
FUNDAMENTOS: As micoses superficiais e subcutâneas têm alta prevalência e, muitas vezes, caráter crônico, necessitando tratamentos tópicos e/ou sistêmicos com antifúngicos. As drogas de escolha são azóis e alilaminas (terbinafina). É necessário avaliar a eficácia das drogas para tratamento em humanos e em animais. Estudos para avaliar in vitro a ação dos antimicóticos são raros, especialmente, contra fungos filamentosos. OBJETIVO: Avaliar a eficácia in vitro da terbinafina pelo método de disco-difusão contra fungos filamentosos e leveduras agentes de micoses. MÉTODOS: Avaliou-se a ação da terbinafina (0,125µg-100µg) contra dez espécies fúngicas pelos métodos discodifusão e microdiluição/referência, para determinar a concentração inibitória mínima (MIC). RESULTADOS: Observou-se alta sensibilidade à terbinafina em: T. rubrum, M. gypseum, T. mentagrophytes, T. tonsurans, M. canis, C. carrionii e E. floccosum (halo ≥ 40mm com disco de 0,125µg). S. hyalinum e C. parapsilosis foram considerados sensíveis, mas com halos menores. Fusarium spp. apresentou menor sensibilidade (halo=12mm com disco de 2µg; MIC 8µg/mL). CONCLUSÕES: Os resultados reiteram estudos anteriores quanto à alta eficácia da terbinafina em relação a dermatófitos. A técnica de disco-difusão foi de fácil aplicação e adequada na rotina de laboratórios clínicos. BACKGROUND: Superficial and subcutaneous mycoses have a high prevalence and, often, chronic evolution. Therefore, they need extensive treatment with topic and/or systemic antifungal agents. Azoles and alilamines (terbinafine) are first-choice drugs to treat human and animal infections. Thus, evaluation of the efficacy of these drugs is important for a successful treatment. However, there are few studies that evaluate the in vitro activity of antifungal agents. OBJECTIVE: To evaluate the in vitro efficacy of terbinafine activity against filamentous fungi and yeasts that cause mycoses. METHOD: The in vitro activity of terbinafine (0.125-100µg) against 10 fungi species was evaluated by the diskdiffusion and microdilution/reference methods to determine the Minimum Inhibitory Concentration (MIC). RESULTS: We found a high susceptibility to terbinafine in: T. rubrum, M. gypseum, T. mentagrophytes, T. tonsurans, M. canis, C. carrionii and E. floccosum (halo ≥ 40mm with 0.125µg disk). S. hyalinum and C. parapsilosis were considered susceptible, but less than the others. Fusarium spp. showed the lowest susceptibility (halo=12mm with 2µg disk; MIC 8µg/mL). CONCLUSIONS: The results of this research confirm previous findings about the efficacy of terbinafine. The drug was shown to be highly effective to treat dermatophyte infections. The disk-diffusion method was easy to use and is a suitable technique for routine use in clinical laboratories.